Activation of arginine vasopressin receptor 1a reduces inhibitory synaptic currents at reciprocal synapses in the mouse accessory olfactory bulb - Taniguchi, Mutsuo; Murata, Yoshihiro; Yamaguchi, Masahiro; Kaba, Hideto (Frontiers in Cellular Neuroscience, 2024)
Central arginine vasopressin (AVP) facilitates social recognition and modulates many complex social behaviors in mammals that, in many cases, recognize each other based on olfactory and/or pheromonal signals. AVP neurons are present in the accessory olfactory bulb (AOB), which is the first relay in the vomeronasal system and has been demonstrated to be a critical site for mating-induced mate recognition (olfactory memory) in female mice. The transmission of information from the AOB to higher centers is controlled by the dendrodendritic recurrent inhibition, i.e., inhibitory postsynaptic currents (IPSCs) generated in mitral cells by recurrent dendrodendritic inhibitory inputs from granule cells. These reports suggest that AVP might play an important role in regulating dendrodendritic inhibition in the AOB. To test this hypothesis, we examined the effects of extracellularly applied AVP on synaptic responses measured from mitral and granule cells in slice preparations from 23--36-day-old Balb/c mice. To evoke dendrodendritic inhibition in a mitral cell, depolarizing voltages of -70 to 0 mV (10 ms duration) were applied to a mitral cell using a conventional whole-cell configuration. We found that AVP significantly reduced the IPSCs. The suppressive effects of AVP on the IPSCs was diminished by an antagonist for vasopressin receptor 1a (V1aR) (Manning compound), but not by an antagonist for vasopressin receptor 1b (SSR149415). An agonist for V1aRs ([Phe 2 ]OVT) mimicked the action of AVP on IPSCs. Additionally, AVP significantly suppressed voltage-activated currents in granule cells without affecting the magnitude of the response of mitral cells to gamma-aminobutyric acid (GABA). The present results suggest that V1aRs play a role in reciprocal transmission between mitral cells and granule cells in the mouse AOB by reducing GABAergic transmission through a presynaptic mechanism in granule cells.